Analysis Effect Of Thick Ballast On Track Quality Index (TQI) Value Route Wonokromo – Mojokerto - Untung Subarkah; Hera Widyastuti; Catur Arif Prastyanto (Sekretariat Badan Kebijakan Transportasi, Formerly by Puslitbang Transportasi Laut, Sungai, Danau, dan Penyeberangan, 2021)
In Operational Area 8 Surabaya there are several railway lines, one of which is the Wonokromo - Mojokerto line. This lane has a fairly heavy train traffic frequency including the connecting lane south. This will affect the quality of roads on the Wonokromo - Mojokerto line. To assess damage to a railroad seen from several aspects in the structure of the railroad. These aspects are the structure of the railroad, the structure of the railroad and the geometrical structure of the railroad. In Indonesian railways, the railroad uses railroad geometry consisting of several parameters (track gauge, cant, longitudinal level, and lateral level.) as a basis for assessing railroad quality. In this study will analyze the structure of the railroad under the thickness of the ballast to the Track Quality Index (TQI). In this study using a simple linear regression analysis to determine the variation of the thickness of the ballast to TQI. From the results of the analysis conducted, obtained thickness changes that occur in ballast that affect the value of the Track Quality Index (TQI). Where the greater ballast, the greater the value of TQI.